2021
DOI: 10.1080/03007995.2021.1918073
|View full text |Cite
|
Sign up to set email alerts
|

Economic burden of treatment-resistant depression among veterans in the United States

Abstract: Objective: Evidence is limited on the economic burden associated with treatment-resistant depression (TRD) among US veterans. We evaluated the economic burden among patients with major depressive disorder (MDD) with and without TRD, and those without MDD in the Veterans Health Administration (VHA).Methods: Three cohorts were identified using VHA claims data (01APR2014-31MAR2018).Patients with MDD (aged ≥18) who failed ≥2 antidepressant treatments of adequate dose and duration were defined as having TRD; patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Out of 8.9 million treated MDD patients in the US, about 2.8 million are estimated to have TRD, which amounts to an overall cost of almost $44 billion in treating these patients 4 . Compared to treatment responsive individuals, those with TRD are 20% 5 to 30% 6 more expensive to treat, account for as much as 70% 7 more emergency department visits, outpatient visits, and prescriptions 8 , and are 40% more likely to be hospitalized 9 . These individuals have greater lost productivity 10 , higher rates of permanent disability 11 , and higher levels of suicide attempts and completed suicide 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Out of 8.9 million treated MDD patients in the US, about 2.8 million are estimated to have TRD, which amounts to an overall cost of almost $44 billion in treating these patients 4 . Compared to treatment responsive individuals, those with TRD are 20% 5 to 30% 6 more expensive to treat, account for as much as 70% 7 more emergency department visits, outpatient visits, and prescriptions 8 , and are 40% more likely to be hospitalized 9 . These individuals have greater lost productivity 10 , higher rates of permanent disability 11 , and higher levels of suicide attempts and completed suicide 12 .…”
Section: Introductionmentioning
confidence: 99%
“…This evaluation encompassed tangible costs, such as healthcare expenditures and medication costs, and expenses associated with commuting to healthcare facilities, as well as intangible costs, including productivity loss and work absenteeism. Previous literature found that the economic burden of TRD was significantly higher than that of non-TRD [ 11 , 22 25 ]. The annual incremental burden of TRD in the United States was approximately $43.8 billion.…”
Section: Introductionmentioning
confidence: 99%
“…This included tangible and intangible costs of TRD, such as productivity loss, work loss, and cost of commuting to the hospital. Previous literature found that the economic burden of TRD was signi cantly higher than that of non-TRD depressive disorders (Gibson et al, 2010;Olchanski et al, 2013;Pérez-Sola et al, 2021;Shah et al, 2021;Szukis et al, 2021). The national economic burden of TRD in the USA was estimated to cost 43.8 billion dollars annually, of which 47.2% account for the burden of MDD medications (Zhdanava et al, 2021).…”
Section: Introductionmentioning
confidence: 99%